Urgensi Nilai Taksiran terhadap Motivasi Nasabah dalam Transaksi Gadai Emas - Semawati Semawati; Asmarani Asmarani (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study aims to determine whether the estimated value set by pawn service providers is one of the considerations for customers in pawning their gold and whether the estimated value plays an important role in motivating customers in gold pawning transactions at certain pawnshops. The results of the study show that 1) Estimated value is a consideration for customers to pawn their gold at a pawnshop that has a high estimated value. But not only the estimated value is taken into consideration because some gold pawn customers choose a pawnshop to pawn gold based on relatively low maintenance costs. In this case, it proves that not only the estimated value that is taken into consideration, customers make gold pawning transactions but there are several other considerations such as maintenance costs. 2) The estimated value of gold plays an important role in motivating customers to pawn gold at a pawnshop because the estimated value is a reference for customers in obtaining loans.